Synthesis and Characterization of New Heterocyclic Liquid Crystals - D. Srividhya; S. Manjunathan; S. Thirumaran (E-Journal of Chemistry)
This investigation enumerates the synthesis and mesomorphic properties of 1,2,3-triazole containing azobenzene liquid crystals. In these liquid crystals the methylene chain length at non polar end was varied from six to ten carbons to investigate the association properties of non polar chain on the melt. The compound was designed to have a polar ether chain at the other side of the molecule adjacent to the triazole ring and synthesized to enhance the dipolar interactions. These alterations in chemical structure produce two series of new liquid crystalline compounds with each series containing five variations in the methylene chain. The structure of the target compounds and the intermediates were confirmed by the 1H NMR, 13C NMR and IR spectral techniques. Polarized microscopic studies revealed that all the compounds in the series exhibited enantiotropic liquid crystalline properties. This was further confirmed using differential scanning calorimetric experiments. The energy minimized structure supports the mesogenic behavior of the structure.